2021
DOI: 10.1007/s41347-021-00209-3
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Contemporary Perspectives on Videoconference-Based Therapy—Prioritising Indigenous and Ethnic Minority Populations in the Global South

Abstract: An integrative literature review was undertaken as a means of drawing together contemporary perspectives on the outcomes and affordances of videoconference-based therapy. This review was conducted in a way which placed emphasis on the need for mental healthcare strategies which are mindful of the cultural and social needs of indigenous and ethnic minority populations, particularly those situated in the Global South. The review was undertaken using an inverse funnelling approach which sought to prioritise liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…A potential solution to the problem of inadequate time for individual face‐to‐face interventions by busy clinicians might be referral for telehealth treatment by psychosocial oncology professionals working remotely. Treatment by phone or video at parent/patient convenience has proven to be well received and could be key to solving the problem of access, time, and space 19,20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential solution to the problem of inadequate time for individual face‐to‐face interventions by busy clinicians might be referral for telehealth treatment by psychosocial oncology professionals working remotely. Treatment by phone or video at parent/patient convenience has proven to be well received and could be key to solving the problem of access, time, and space 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment by phone or video at parent/patient convenience has proven to be well received and could be key to solving the problem of access, time, and space. 19,20 BI is a well-established, evidence-based psychosocial intervention in pediatric oncology that has been replicated several times. Although the research version was delivered by research assistants with little prior clinical training or experience in pediatric oncology, clinical implementation has been a challenge.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Google Scholar was the first port of call in this regard. Though other studies (e.g., Classen et al, 2020) have shown the utility of this platform, our trial searches found little that met the criteria for inclusion, and what was found had already been identified elsewhere.…”
Section: Google Scholar Theses and Dissertations Textbooksmentioning
confidence: 99%
“…There are many terms for the use of video in counselling and psychotherapy, including online counselling/therapy, teletherapy, e‐counselling/e‐therapy, and videoconference‐based therapy. Classen et al (2020) provide a helpful definition that was used to frame the present study: “we were primarily interested in videoconference‐based forms of online therapy, wherein a client and therapist use software to interact with one another via synchronous audio and visual communication” (p. 546). Smith et al (2022) also recognise the difficulty of empirical investigation in this area of practice, given the lack of standardisation in terminology.…”
Section: Terminologymentioning
confidence: 99%
“…In particular a kaupapa Māori research methodology may have yielded more nuanced findings about the experience for Māori and Pasifika students. As it stands, there is a significant gap in the literature about the cultural implications of online therapy for tangata whenua and Pasifika populations (Classen et al, 2021).…”
Section: Limitations and Recommendationsmentioning
confidence: 99%